Case 3694: Pomachilius variegatus Schwarz, 1904 (Insecta, Coleoptera, Elateridae): proposed conservation of the specific name by suppression of the name Aeolus variegatus Curtis, 1839 - Johnson, PJ (Bulletin of Zoological Nomenclature)
The purpose of this application, under Articles 23.9.3 and 81 of the Code, is to conserve the specific name Pomachilius variegatus Schwarz, 1904 (Insecta, Coleoptera, Elateridae) by suppression of the name Aeolus variegatus Curtis, 1839 a senior secondary homonym, and a subjective junior synonym of Pomachilius subfasciatus (Germar, 1824). Stability of taxonomy and nomenclature would best be served by suppressing the senior homonym.
Keywords: Nomenclature; taxonomy; Coleoptera; ELATERIDAE; Aeolus variegatus; Pomachilius variegatus; Pomachilius subfasciatus; click beetle; Neotropical